1980
DOI: 10.1002/bjs.1800671006
|View full text |Cite
|
Sign up to set email alerts
|

The recovery of intestine after ischaemic injury

Abstract: A reproducible model of reversible segmental ischaemia was used to evaluate methods of predicting intestinal viability after the release of strangulation. Visual assessment in the immediate period after reperfusion and at "second-look' 24 hours later was inaccurate in identifying recoverable bowel. A Doppler probe used to detect the return of pulsatile blood flow was overpredictive of necrosis. The pattern of surface fluorescence after injection of the supravital dye fluorescein increased the accuracy of predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

1981
1981
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…Numerous techniques, including Doppler ultrasonography15, laser tissue blood flowmetry16, NIR spectroscopy17, charged‐couple device microscopy18, pulse oximetry19 and fluorescence angiography using fluorescein injection20, have been evaluated for clinical use during bowel surgery. Although fluorescein angiography was shown to be superior to Doppler ultrasonography21, 22, this optical technique is not currently used because visible fluorescence emission requires that all other operating room lights be off. Additionally, time to complete an examination was relatively long and repeat examination was hindered by fluorescein's long half‐life.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous techniques, including Doppler ultrasonography15, laser tissue blood flowmetry16, NIR spectroscopy17, charged‐couple device microscopy18, pulse oximetry19 and fluorescence angiography using fluorescein injection20, have been evaluated for clinical use during bowel surgery. Although fluorescein angiography was shown to be superior to Doppler ultrasonography21, 22, this optical technique is not currently used because visible fluorescence emission requires that all other operating room lights be off. Additionally, time to complete an examination was relatively long and repeat examination was hindered by fluorescein's long half‐life.…”
Section: Discussionmentioning
confidence: 99%
“…However, the visual assessment of ischemic intestine under white light is unreliable in both open and laparoscopic conditions [3,7,11]. The adjuvant use of fluorescein dye has been shown to increase the sensitivity and specificity of clinical judgement alone in open laparotomies for intestinal ischemia, and it is more accurate than other operative means of diagnosis, such as Doppler flowmetry [1,2,6,7,10,14].…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescein dye is inexpensive, readily available, and safe [2,5,7,11,12,18]. Gorey [6] reported a sensitivity of 96% and a specificity of 95% with the use of fluorescein fluorescence in open exploration for mesenteric ischemia in the rat model. Pearse et al [17] found similar results in the early assessment of intestinal ischemia in the canine model with a sensitivity of 88%.…”
mentioning
confidence: 99%
“…The remainder were viable by both tests and were preserved. Gorey (1980) revives interest in the use of fluorescein to define bowel viability and showed in rats that fluorescence was 95 % accurate in predicting viable and non-viable bowel.…”
Section: Intestinal Obstructionmentioning
confidence: 99%